Bibliotherapy: Awareness and Use among Medical Library Workers in Ogbomoso - Olajide John Abiola; Adebola Aderemi Olatoye (PT Mattawang Mediatama Solution, 2023)
The concept of bibliotherapy draws upon various academic fields, such as medicine, literary criticism, librarianship, and psychology, to promote the use of reading as a therapeutic tool. This study aimed to explore the extent to which medical library workers are aware of and utilize bibliotherapy. Using a descriptive survey design, the study employed Slovin's formula and simple random sampling to select 24 respondents from a population of 45 medical library workers. The findings revealed that the medical library workers had a good understanding of bibliotherapy. Therefore, it is recommended that they should be equipped with the necessary skills to provide bibliotherapy services, and given the opportunity to practice it.